2008
DOI: 10.1080/10599240801985589
|View full text |Cite
|
Sign up to set email alerts
|

Bone Quantity and Quality of Youths Working on a Farm—A Pilot Study

Abstract: This study investigated the effect of farm-related activities on the bone health of youths. Bone quantity and bone quality were quantitated in 36 adolescents-18 youth with a history of working on farms and 18 youth not involved in farm-related activities. Bone quantity as depicted by bone mineral density (BMD) was measured with dual-energy x-ray absorptiometry. Bone quality was characterized with biomechanical measures based on bone geometry and measures of dynamic bone shock absorption (BSA) properties. Dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…We calculated these variables in the subset of our patients using the method and software published by Riancho et. al and compared those to data from the literature (29;37). While our fracture group showed lower values for section modulus, compressive strength, cortical thickness and higher values for buckling ratio than the non-fracture group, these differences were not statistically significant (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated these variables in the subset of our patients using the method and software published by Riancho et. al and compared those to data from the literature (29;37). While our fracture group showed lower values for section modulus, compressive strength, cortical thickness and higher values for buckling ratio than the non-fracture group, these differences were not statistically significant (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Using the above-mentioned structural bandwidth and resonance frequency method, ζ were obtained directly from a measured FRF (34;35). We have used these variables successfully in our earlier studies in adults as well as adolescents (25;37). As waveforms vary due to the frequency content of the force transient and acceleration transient the ratios of heel-strike force and the accelerations can only be consistent on a frequency-by-frequency basis and that is the rationale for using the frequency domain or FRF analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…youths who live and work on farms and youths who do not (Bhattacharya et al, 2007). Previous studies have shown that work-related factors such as repetitive kneeling, squatting, and heavy lifting are contributors to the development of osteoarthritis and other types of MSDs.…”
Section: Msds In Children and Adolescent Farmworkersmentioning
confidence: 97%
“…The main hypothesis for this study was that bone mass, static biomechanical properties, and dynamic shock absorption properties do not differ between youths involved in physically demanding farm-related tasks compared with those who do not work on farms. The study showed that dynamic bone response measures provide preliminary evidence that farm-related physically demanding tasks lead to changes that may predispose teenagers to degenerative skeletal disorders later in life (Bhattacharya et al, 2007).…”
Section: Msds In Children and Adolescent Farmworkersmentioning
confidence: 99%